Les Routes de la soie. Entre réalités et imaginaires. - Peter Frankopan (Cahiers d’histoire.)
The very name « Silk Roads » evokes impressions and ideas of a mysterious, elusive and exotic world. However, these civilizations are still poorly known to the general public and little taught in the West. The author, a specialist in the Silk Roads and global history, traces the history - between myth and reality - of these Roads, and evokes their importance for the Europeans themselves. He underlines the major role in the history of great civilizations such as the Mongolian Empire, and gives his thoughts on the taking of power by the West over the centuries, and the necessary reconnection between East and West.